Drought resistance of introgressive spring common wheat lines with genetic material of tall wheatgrass - L. Ya. Plotnikova; A. T. Sagendykova; S. P. Kuzmina (Труды по прикладной ботанике, генетике и селекции)
Background. To breed drought-resistant cultivars of common wheat1 (Triticum aestivum L.), it is important to use the gene pools of its relatives, including tall wheatgrass Thinopyrum ponticum (Podpěra) Z.-W. Liu & R.- C. Wang (= Agropyron elongatum (Host) Beauv.).   Materials and methods. The introgressive lines of spring common wheat with T. ponticum genetic material and standard cultivars were studied in the field in the southern forest-steppe of Western Siberia using generally recognized methods. The ecological plasticity of cultivars and introgressive lines by grain yield and yield components was calculated according to the method of S. A. Eberhart and W. A. Russell. During the research period, there was a prolonged drought in 2012, and irregular short severe droughts occurred in 2013, 2014, and 2017.   Results. An analysis of the ecological plasticity of standard cultivars adapted to the regional conditions showed that cv. ‘Pamyati Azieva’ corresponded to the extensive type, and cvs. ‘Duet’, and ‘Erythrospermum 59’ corresponded to the intensive type. Under drought conditions, the grain yield of cv. ‘Pamyati Azieva’ was determined by the stable development of productive tiller number, seed number and grain yield per main ear, but plasticity in 1000 grain weight was observed. Cvs. ‘Duet’ and ‘Erythrospermum 59’ showed ecological plasticity due to the adaptive development of two or three yield components. Introgressive lines exceeded the standard cultivars in grain yield (1.1–2.2 times) in dry seasons. Five lines were similar to cv. ‘Pamyati Azieva’ in plasticity and stability, and under drought conditions they demonstrated high and stable development of three or four yield components. The intensive lines formed their yield due to the compensatory development of three yield components in different combinations.   Conclusion. Introgressive lines with T. ponticum genetic material are valuable for breeding spring common wheat cultivars with various drought-adaptation mechanisms.